How is REDD+ unfolding in southern Africa’s dry forests?: a snapshot from Mozambique - Wertz-Kanounnikoff, Shiela; Sitoe, A.; Salomão, A. (Center for International Forestry Research, 2011)
Mozambique has high forest cover, a high deforestation rate and severe forest degradation. It is also one of the poorest and most vulnerable countries in the world. Therefore, Mozambique requires a pro-poor REDD+ model that progressively widens its scope to include agriculture and adaptation. Mozambican experts have drafted a national REDD+ strategy, which is currently undergoing government consultation, with public dissemination to follow later in 2011. The main REDD+ initiatives in Mozambique include a Norwegian-funded South–South cooperation programme with Brazil designed to support REDD+ strategy development, and a Japanese-funded readiness initiative on monitoring, reporting and verification and reference levels. Mozambique has a tradition of stakeholder consultation and relatively inclusive processes. However, to improve the content and acceptance of the REDD+ strategy and subsequent related legislation, greater capacity-building efforts and consultations are needed, especially at subnational levels, amongst communities and in the private sector. Important lessons for REDD+ benefit sharing can be drawn from Mozambique’s innovative—yet still underimplemented—20% timber royalty distribution mechanism, as well as the two ongoing carbon forestry payments for environmental services schemes. Securing financing for REDD+ will be a challenge, and funding REDD+ implementation phases will require pooling resources from different sources. Implementation of a solid, well-developed REDD+ strategy can serve as a powerful framework to attract and coordinate such long-term financing for REDD+.